Les Fractures De La Patella Chez L’adulte - F., Gnandi-Piou; F., Akondo HK; A., Lagnéblé; S., Tsolenyanu; K., Amakoutou; A., Walla; A., Abalo; AM., Dossim (European Scientific Journal, ESJ, 2018)
Objectives: to determine the epidemiological aspects, the different techniques of surgical fixation of the patella fractures and the results. Patients and methods: this was a retrospective study from January 1, 2013 to December 31, 2017 and included the records of patients aged 15 years and older surgically treated for a patella fracture in our center. Results: The work involved 36 patients including 28 men (77.8%) and 8 women (22.2%) with a mean age of 35.9 years. High way trauma were the first cause of these fractures. Fractures were open in 44.4% of cases. Type II according to Ricard and Moulay classification was the most represented with 58.3% of cases. The majority of the patients, 80.5%, were treated by rigging. Five (5) cases of hematoma, one (1) postoperative infection, and three (3) cases of knee stiffness complicated the short- and medium-term follow-up. With an average follow-up of 2 years 6 months, radiologically, normal consolidation was achieved in 86.1% of cases. Two (2) cases of delayed consolidation and three (3) cases of nonunion have been noted. Three (3) cases of patellofemoral osteoarthritis appeared at two years. From the functional point of view, according to the Bosman score, 27.8% were excellent, 63.9% were good, 8.3% were bad, and the cable rigging seemed to give excellent and good results. Conclusion: the treatment of transverse fractures of the patella must be exclusively surgical. Guying is an osteosynthesis technique of choice. Nevertheless complications including knee stiffness, non-union and patellofemoral osteoarthritis are not uncommon